Gestión Administrativa de la Lubricadora Zm del Cantón Jujan en el periodo 2021. - Posligua Martínez, Aquiles Nexar (2022)
The present takes place in the Zinemia Lubricator located in the Alfredo Baquerizo Moreno - Jujan canton, which focuses on providing washing, greasing, spraying, oil changes, foam bath, vacuum, graphitized shower services, in addition to, the sale of lubricants and additives, the same one that will be part of this research that has the objective of analyzing the administrative management within the Zinemia Lubricator of the Jujan canton in the period 2021, with the help of the line is of this work is the Financial Management, Administrative, Tax, Audit and Control and the Business and Public and Private Institutions subline, given that it constitutes a business model in the private sector, on the other hand, the research methodology used was descriptive and inductive research, at the same time , techniques were used for the collection of information, the interview technique applied to the manager of the lubricator and the surveys carried out on the employees, where it was obtained As a result, the situation around managed management shows various anomalies that the company has such as: the lack of managing the lubricator, the absence of not having adequate inventory control and the lack of experience for the development of activities such as customer service. , by employees that has repercussions on the service provided to the company's customers.